Genomic insights into Halorubrum ezzemoulense strain TC23: Genetic basis for halophilic traits and biotechnological potential - Kesbiç, Fevziye Işıl (SAGE Publications, 2025)
Objective This study aimed to explore the genomic features of Halorubrum ezzemoulense strain TC23, an extreme halophilic archaeon isolated from the Ayvalık Saltern in Türkiye, with a focus on its halophilic adaptations and potential biotechnological applications. Methods Whole-genome sequencing was performed using the Illumina NovaSeq 6000 platform. In silico analyses were conducted using tools such as Prokka and eggNOG-mapper for structural and functional annotation, including gene ontology (GO), Clusters of Orthologous Groups (COG), and Kyoto Encyclopedia of Genes and Genomes pathway predictions. Taxonomic validation was performed with TYGS, and the genome was compared to related strains using digital DNA–DNA hybridization (dDDH), average nucleotide ıdentity, and phylogenomic tree construction. Results The genome comprised 3755 genes, including 3551 coding sequences. Key genes involved in osmoregulation, DNA repair, and salt tolerance were identified. Functional categorization based on COGs indicated pathways associated with hypersaline survival. Comparative genomic analysis confirmed the strain's placement within Hrr. ezzemoulense . Notably, the genome encodes extremozymes and stress-response genes relevant to high-salinity and oxidative environments. Conclusions The genomic insights provided by strain TC23 contribute to our understanding of halophilic adaptation mechanisms and highlight its potential in industrial applications requiring salt- and stress-resilient biocatalysts. This study supports future exploration of archaeal genomes as a resource for biotechnological innovation.